Formation of the Khalsa Biradari and Abhed Sikhs: A step towards equality. Or was it?. (2nd October 2021) - Kaur, Kulbir
ABSTRACT: The paper, 1 with the use of the notion of 'purity and pollution, ' analyses the status of the Dalits within the Sikh social order. 'Dalit Sikhs' remained in the background but the act of purification, 'Khande-ki-pahul', was cited as the medium to abolish all differentiation and further, to remove caste distinctions, Khalsa Biradari was formed in 1907. But did this elevated status of the Dalit Sikhs as Khalsa or Abhed Sikhs improve their social standing? Could they leave their past behind and merge seamlessly into the fold of Sikhism?